Curved space plasmonic optical elements - Singh, Danveer; Libster-Hershko, Ana; Shiloh, Roy; Arie, Ady (Optics Letters, 2019)
We have designed and experimentally studied non-planar curved space plasmonic optical elements. Three different smooth curved space plasmonic structures were studied: a dome that acts either as a focusing element or as a deflector for plasmonic beams, a cone that acts as a plasmonic prism, and a tapered book cover that alters the size of a plasmonic guided wave. The functional mechanism of these elements relies purely on the curvature-induced effective potential and does not require any additional dielectric layer for shaping the plasmonic beams. The curved space plasmonic elements open exciting new possibilities for guiding, focusing, deflecting, and controlling the propagation of plasmonic beams in a compact manner.
Created from Fastlane, Scopus look-up